ANALISIS KELAYAKAN USAHA TANI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS JAGUNG PADA LAHAN KERING DI KECAMATAN LABANGKA KABUPATEN SUMBAWA - Nurwahidah, Siti; Darwanto, Dwidjono Hadi; Masyhuri, Masyhuri; Waluyati, Lestari Rahayu (Jurnal Ilmu-Ilmu Pertanian, 2015)
This research was intended to identify productivity and income of corn farming in dry land at Sumbawa Regency. It used descriptive analysis method. The research was done with survey technique. Sample was taken using random sampling with 100 respondents. Research site was determined purposively in Labangka district. It used Cobb-Douglas production factor analysis and financial analysis (cost, revenue and income). The result indicated that average productivity was 6.092 ton/ha with average cost of Rp 2,912,994/ha, average revenue or 13,392,755/ha and average profit of 10,479,762/ha. Factors affecting production significantly are seed amount, urea fertilizer amount, insecticide amount, experience in corn farming, and activeness in extension program. R/C ratio of 4.6 means that corn farming in dry land in Labangka district is profitable and feasible to continue.